Construction and Communication of Harbin's City Image under the Background of New Media - Zou, Zhuoheng (Transactions on Economics, Business and Management Research, 2024)
The rapid rise of short video platforms has injected new vitality into the construction and communication of city images. In the article, Harbin is the research object. Firstly, it analyzes the communication characteristics of the city image under the background of new media. Secondly, from the communication subject, communication content, communication channels and communication effects, the paper deeply analyzes the characteristics of Harbin's image communication, explores the close relationship between Harbin's popularity and new media, and reveals the potential laws and internal motivations.